Development of inorganic nanoparticle glycoconjugate enhanced cotton fabrics for multi-drug-resistant Pseudomonas aeruginosa bacterium - Ardanur Küçük; Zehra Taşdelen; Şevval Güney; Sedanur Sel; Esinti İrem Demirbaş; Fatma Öztürk Kırbay; Sedanur Sancak; Maarja Otsus; Hafize Dilek Tepe; Kaja Kasemets; Çetin Kılınç; İdris Yazgan (The Microbe)
Surface modification of cotton fabrics is required to advance their inherent properties in the development of antibacterial cotton fabric-based biomaterials. In this study, an antibacterial cotton fabric for multidrug resistant Pseudomonas aeruginosa species was developed. To do this, lactose and galactose derivatives were used to synthesize silver (Ag) and gold (Au) nanoparticle glycoconjugates (NP-GCs) to functionalize the cotton fabrics to target the carbohydrate binding proteins LecA and LecB lectins found on P. aeruginosa. The three lactose derivatives (i.e. Lactose sulfanilic acid (LSA), Lactose 5-aminosalicylic acid (L5AS) and Lactose 4-(4-aminophenyl) butyric acid (L4APB)) gave stable AgNP-GCs and AuNP-GCs while Galactose 4,4’-oxydianiline (GODA) allowed only stable AuNP-GCs synthesis. The cotton fabrics were pretreated to eliminate non-cellulosic parts to obtain scoured cotton fabrics (sCFs) for surface functionalization with AgNP-GCs and AuNP-GCs. Three different approaches (i.e. direct adsorption or adsorption through sulfhydryl group on sCFs and in situ synthesis) were followed to obtain AgNP-GCs functionalized cotton fabrics while AuNP-GCs functionalization was performed only through in situ synthesis. AgNP-GCs and AuNP-GCs were in situ synthesized on the sCFs under heat-treatment, and homogenous surfaces with high load of AgNP-GCs or AuNP-GCs were obtained. AuNP-GC-sCF were then functionalized with Colistin in order to add antibacterial property for P. aeruginosa. The colloidal AgNP-GCs, and in situ synthesized AgNP-GC-sCF and AuNP-GC-sCF showed strong antibacterial activity for P. aeruginosa. The formulations were then tested for gram (-) Escherichia coli and Klebsiella pneumoniae, and gram (+) Staphylococcus epidermidis to evaluate whether they have wide-spectrum antibacterial activity. While the colloidal AgNP-CGs showed similar high toxicity for these species in comparison to P. aeruginosa, only LSA_AgNP-GC-sCF and LSA_AgNP-GC-sCF showed 100 % growth suppression for E. coli, K. pneumoniae and S. epidermidis. The Colistin functionalized AuNP-GC-sCFs were also tested for Colistin resistant K. pneumoniae, and > 99 % growth suppression was obtained. We also tested whether the surface charge of the AuNP-GCs affect their interactions with P. aeruginosa using confocal laser scanning microscopy, where clear interactions were observed for GODA_AuNPs. These early results revealed that inorganic nanoparticle glycoconjugates can be designed to develop antibacterial cotton fabrics through designing chemistry that can target lectins on bacterial membranes.